On the Symmetry of Case in Conjunction. (4th October 2019) - Weisser, Philipp
Abstract: In this article, I argue that all of the conjuncts in nominal conjunction always bear the same case. Apparent counterexamples, where conjuncts seem to differ in morphological case marking, are due either to a misanalysis of the underlying syntactic structure or to superficial morphological processes that create the impression of a difference in case marking. Once we control for phenomena of this sort (namely &P clitics, suspended affixation, and allomorphy), we find that case marking in nominal conjunction is always symmetric. This finding is in stark contrast to the phenomenon of ϕ agreement, which is known to exhibit asymmetries in conjunction. I show that the Chomskyan account of case assignment, according to which case arises only as a reflex of ϕ agreement, cannot account for this mismatch without stipulative assumptions. The pattern follows straightforwardly, however, if we assume that case assignment proceeds on the basis of syntactic structure while ϕ agreement can be either syntactic or postsyntactic. Finally, I show that the generalization established can be used as a simple diagnostic to distinguish syntactic case‐marking alternations from morphological ones.